Application of Financial Cloud in the Sustainable Development of Smart Cities - Yangchun Cao; Guangyu Zhang; Chunyao Ou (Complexity)
This article first investigates the status of financial cloud development in smart cities and studies the sustainable development of smart cities. Secondly, it investigates the construction of the evaluation model, using the power of the financial cloud, through exploratory factor analysis, selecting the principal component analysis method to extract the factors, for screening and dimensionality reduction of the indicators, and making hypotheses. We used confirmatory factor analysis to establish the structural equation. The measurement model analyzes and validates the assumptions of the previous stage and finally determines the sustainable development evaluation index system. Then, starting from the scoring coefficient matrix of the exploratory factor analysis of the final model, the variance contribution rate of each common factor is weighted to construct a comprehensive evaluation model to calculate the comprehensive evaluation score. For the comprehensive evaluation score of the sustainable development level of the smart city, SPSS software performs cluster analysis, performs regional clustering, and determines the level of urban development. Finally, by comparing the sustainable development levels of smart cities, the related causes of the gaps are analyzed. Key factors affecting the sustainable development of smart cities are identified, and corresponding countermeasures are proposed.